Outcomes of radiocephalic fistula created by nephrologists. Issue 6 (November 2019) - Prasad, Narayan; Thammishetti, Venkatesh; Bhadauria, DS; Kaul, Anupama; Sharma, RK; Srivastava, Aneesh; Gupta, Amit
Introduction: Arteriovenous fistula is considered as gold standard access for maintenance hemodialysis. Due to increasing burden of end-stage renal disease requiring dialysis, it is important for nephrologists to complement creation of arteriovenous fistula to meet the demand. Methods: This retrospective study was designed to assess the outcomes of arteriovenous fistula made by nephrologists at a tertiary care center from North India. The study included all radiocephalic arteriovenous fistula performed by nephrologists between November 2015 and January 2017. All arteriovenous fistulas were performed in patients whose duplex ultrasonography revealed both arterial and venous diameter of at least 2 mm. Data were collected with regard to age, gender, dialysis status, basic diseases, co-morbidities, and mineral bone disease parameters. The predictors of the primary and secondary patency rates were analyzed. Results: Five hundred patients (age 39.3 ± 14.4 years; 82.4% males; 21.6% diabetics) were included. In total, 83 (16.6%) patients had primary failure and 31 (7%) patients had secondary failure. Diabetes was associated with poor primary and secondary patency rates. Mean survival among the patients without primary failure was 11 months. The primary patency rates at 3, 6, 12, 18, and 21 months were 82%, 78%, 73%, 70%, and 70%, respectively. Conclusion: To conclude, the outcomes of radiocephalic arteriovenous fistulas created by nephrologists are at par with historic outcomes.